Interaction between diabetes-associated disorders of the salivary glands and oral mucosa (literature review) - S. S. Tkachuk; O. V. Tkachuk; A. A. Galagdina; M. A. Povar; O. V. Yasinska (Kazimierz Wielki University, 2020)
The aim of the study: to analyze literature sources concerning interaction between pathogenesis of lesions of the salivary glands and oral mucous membrane in patients suffering from diabetes mellitus (DM).   Conclusion. Analysis of the current literature is quite explicit on the point concerning interdependence of lesions of the salivary glands and morphofunctional changes of the oral mucosa with diabetes mellitus.